2022
DOI: 10.3390/su142416333
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Challenges in the Swedish Urban Planning Process: A Case Study about Digitalization

Abstract: While the populations of cities continue to grow, institutions are demanding more sustainability in urban development, leading to a great increase in the complexity of urban planning. The need to consider social, legal, environmental, and economic parameters challenges the traditional urban planning processing in favor of an optimized and automated process. Generative design has the potential to optimize the design phase by automatically generating spatial design solutions and analyzing them in the design phas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
(55 reference statements)
0
1
0
Order By: Relevance
“…Previous authors have shown that planned city projects can offer a range of benefits for sustainable urbanization, including the development of efficient and sustainable transportation systems, the integration of renewable energy technologies, and the promotion of low-carbon development [13,14]. However, these projects also present a number of challenges, including the need for effective risk management to ensure that they are financially, environmentally, and socially sustainable.…”
Section: Planned Cities As a Tool For Sustainable Urbanizationmentioning
confidence: 99%
“…Previous authors have shown that planned city projects can offer a range of benefits for sustainable urbanization, including the development of efficient and sustainable transportation systems, the integration of renewable energy technologies, and the promotion of low-carbon development [13,14]. However, these projects also present a number of challenges, including the need for effective risk management to ensure that they are financially, environmentally, and socially sustainable.…”
Section: Planned Cities As a Tool For Sustainable Urbanizationmentioning
confidence: 99%